066 MODIFICATION OF THE EUROPEAN HEART RHYTHM ASSOCIATION AF SYMPTOM SCORE IMPROVES DISCRIMINATIVE ABILITY: A VALIDATION STUDY. (24th May 2013) - Wynn, G J; Webber, M; Cullen, D; Hutson, T; Modi, S M; Pettit, S J; Hawkins, N M; Barker, D; Hall, M C S; Snowdon, R; Waktare, J E P; Todd, D M; et al.
Abstract : Introduction: The European Heart Rhythm Association (EHRA) Score for symptoms in Atrial fibrillation (AF) was proposed in 2007 but thus far has not been validated, yet features in European Society of Cardiology 2010/2012 guidelines. Anecdotally, many clinicians feel the jump from class 2 (mild) to class 3 (severe) misses an important step (moderate) where intervention may be more likely to be considered. Methods: Consecutive patients identified as having AF as their primary consultation reason for attending Heart Rhythm clinics at a large cardiovascular centre in the UK completed general (EQ5D) and AF-specific (AFEQT) Quality of Life (QoL) questionnaires. EHRA score was documented by the reviewing clinician, or retrospectively from clinical notes. Patients initially classified EHRA 2 were subsequently re-classified by two clinicians blinded to QoL scores as either 2a (mild: Normal daily activity not affected and symptoms not considered troublesome by patient) or 2b (moderate: Normal daily activity not affected but patient troubled by symptoms). Results: QoL and symptom data was collected on 362 patients (59% Paroxysmal, 65% Male). Mean QoL scores by EHRA Class are shown in the table and ilustrated in the graph with degree of statistical difference (t test) shown at each grade boundary. There is an important stepwise progression in the AFEQT score as patients progress from EHRA Class 1–4 with a significant difference between 2a and 2b in all QoL measures.Figure 1 Conclusions: Based on AFEQT score and EQ5D Visual Analogue scale this study provides the first validation of the EHRA score. The Modified Score improves discriminative ability and, importantly, health utility is significantly different at the 2a/2b and 2b/3 boundaries, where decisions about AF ablation are likely to be made. Based on utility; invasive treatment for patients graded 2b (or above) is likely to be more cost effective than those graded 2a (where the potential improvement to Class 1 is minimal). We recommend adoption of the modified system, and propose that EHRA 2b be considered the cut point for treatment decisions.